The Application of The Shifting Burden of Proof Principles as an Alternative Consumer Protection Effort Due to Unfair Property Advertising - et al., Dwi Edi Wibowo (International Journal of Advanced Science and Technology, 2019)
In the business world, advertising becomes an important factor in marketing a product. Advertising is identified as a promotional media and introduction to products to be produced or sold to the public. The people must be careful in buying and selling transactions for housing or property. The problem in this study is how is the legal politics of the shifting burden of proof principle in an effort to provide fair consumer protection due to fair property advertising? Research Methods, normative research is research by directing research into positive law and written norms, thus the analysis in this study refers to the applicable laws and regulations namely the Consumer Protection Act No.8 of 1999. The typology includes descriptive research, this study uses literature study, the type of data used is secondary data obtained from literature, primary data through interviews. Conclusion of consumer protection against misleading property advertisements can be preventive by establishing a legal rule that will ensure that consumers can receive legal protection by conducting shifting burden of proof.